Not only age but also tactile perception influences the preference for cosmetic creams applied to the forearm. (4th December 2016) - Trautmann, M.; Wendel, V.; Prinz, D.; Primmel, B.; Willging, G.; Nagorsen, E.; Suckert, A.; Gehm, S.; Brandt, M.; Ballay, P.; Godde, B.
Abstract: Objective: We aimed to examine whether and how age as well as tactile sensitivity and perception had an impact on how women liked richer and lighter creams. Furthermore, the question arose if age and tactile perception had an influence on the ability to distinguish between the creams and how the ability to distinguish between creams influenced the liking of these creams. Methods: A total of 299 female participants were invited to rate how much they liked four different cosmetic creams applied to their forearms. The creams were based on the same base formula but differed with respect to the texture. In order to arouse the impression of more lightness (quasi‐light) or more richness (quasi‐rich), polyethylene particles of different sizes were added to the base formula. First of all, the participants were tested for their tactile sensitivity and perception. Tactile sensitivity was tested by Von Frey filaments, tactile spatial perception by the tactile Landolt ring test and the ability to discriminate surface structures by a sandpaper test. Furthermore, the participants rated the creams with respect to the acceptance, the subjective skin feeling after application and performed paired‐comparison tests. Analyses of variance and regression analyses were applied to the data. Results: In general, participants liked quasi‐rich creams less than quasi‐light creams. However, older women compared to younger women and women with lower tactile performance in comparison with women with higher tactile performance revealed a weaker influence of cream type‐specific acceptance ratings. Further results revealed that young participants perceived the quasi‐light creams (with particles of ~50 μm diameter) as soft and quasi‐rich creams (with particles of ~100 μm and ~165 μm diameter), as coarse. In contrast, this subjective skin feeling after application in participants at age 50 and older did not differ much. Conclusion: Age and tactile perceptual abilities have additive effects on the acceptance of creams with different textures when applied to the forearm.